A review on the health hazards of anabolic steroids. (August 2019) - Horwitz, Henrik; Christoffersen, Thea
Abstract : Summary: In 1935, testosterone was finally isolated and synthesized, and testosterone-analogs soon entered the world of sports. Today, the use of these performance-enhancing agents is no longer confined to the elite sports milieu, and the lifetime prevalence of anabolic steroid use among men is estimated to be around 6%. Unfortunately, these drugs are not without side effects, and the most common somatic adverse drug reactions are gynaecomastia, infertility, testicular dysfunction, and acne. Furthermore, the use of AAS is associated with a variety of psychiatric disorders and antisocial behaviour.